Percutaneous CT-Guided Biopsy of Osseous Lesion of the Spine in Patients with Known or Suspected Malignancy - Lis, Eric; Bilsky, Mark H.; Pisinski, Leszek; Boland, Patrick; Healey, John H.; O’Malley, Bernie; Krol, George (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: CT-guided spinal biopsy (CTGSB) is considered a safe and accurate procedure. Our goal was to determine the accuracy of a CTGSB of osseous spinal lesions in patients with known or suspected underlying malignancy in reference to major variables such as the radiographic appearance of the biopsied lesion and its location within the spinal column.METHODS: We retrospectively reviewed results of 410 consecutive percutaneous CTGSB procedures of osseous spinal lesions. Biopsy was determined to be adequate if diagnostic tissue was obtained (n = 401) or unsatisfactory (n = 9) if only blood without cellular elements was present on final pathologic-cytologic examination.RESULTS: The level of spinal biopsy was cervical in nine patients (2%), thoracic in 123 (31%), lumbar in 164 (42%), and sacral in 96 (25%). The overall diagnostic accuracy of CTGSB was 89%, with a false-negative rate of 11%. Biopsy of lytic lesions yielded an accurate diagnosis in 93% (220 of 236). Despite technical challenges inherent to biopsy of sclerotic lesions, diagnostic accuracy was 76% (63 of 83), although more importantly, 24% (20 of 83) of the results in sclerotic lesions were falsely negative.CONCLUSION: CTGSB of osseous spinal lesions is an important tool in the workup of patients with known or suspected underlying neoplastic disease. However, a negative result must be confirmed with either close follow-up or, preferably, open biopsy, especially in cases of sclerotic lesions for which diagnostic accuracy is decreased and the false-negative rate is high.